Case report: The remarkable response of pembrolizumab combined with RC48 in the third-line treatment of metastatic urothelial carcinoma - Xu, Zhenying; Ma, Jiaman; Chen, Ting; Yang, Yu (Frontiers in Immunology, 2022)
Background Systemic chemotherapy has been the mainstay treatment for locally advanced or metastatic urothelial carcinoma (UC). In the past few years, novel immune checkpoint inhibitors (ICIs) and antibody-drug conjugates (ADCs) have improved the treatment of advanced UC. Case presentation Here, we report systemic therapy of a 68-year-old male diagnosed with HER2 positive (immunohistochemistry 3+), programmed cell death ligand 1(PD-L1) negative metastatic UC, and renal insufficiency. He had encountered numerous metastases and failed first-line platinum-based chemotherapy and second-line treatment with pembrolizumab and trastuzumab. During third-line treatment with RC48 (a HER2 targeting ADC) combined with pembrolizumab, he achieved a rapid partial response (PR) in the first evaluation and subsequent complete response (CR) on PET/CT and long-term progression-free survival (>12 months) at the last follow-up on 25 August 2022. There are no grade 3 or 4 adverse events or aggravations of renal insufficiency during the third-line therapy. Discussion RC48 combined with pembrolizumab demonstrated outstanding efficacy and safety in this HER2-positive metastatic UC patient. ADC combined with ICI is a promising anti-tumor strategy that deserves further exploration in advanced UC.